Softening the Hearts of Business Students: The Role of Emotions in Ethical Decision Making - Jeong, Sophia S.; Sun, Cong (Timothy); Fu, Ping Ping (Journal of management education, 2020)
Business schools face a dilemma of promoting prosocial values while maintaining the principles of self-interest and profit maximization. In response to recent research suggesting that emotions may be the key to ethical decision making, we ask two basic questions: Do emotions make business students more ethical? Is business school education inhibiting ethical decision making? Drawing on theories on moral emotions and ethical decision making, we hypothesize that moral emotions will enhance ethical decision making, whereas hedonic emotions will diminish ethical decision making. Furthermore, we predict that a higher level of business school education will strengthen the negative relationship between hedonic emotions and ethical decision making while weakening the positive relationship between moral emotions and ethical decision making. Using a scenario-based repeated-measure design, we tested our hypotheses with 217 students from secondary schools, undergraduate business majors, and MBA programs in Hong Kong. Multilevel modeling results supported our hypotheses, suggesting that business school students may benefit from education on the unique roles of moral and hedonic emotions in the ethical decision-making process. We conclude with a summary of the theoretical and practical implications of our findings.